The Selection of Oral Antidiabetic Drugs in Type 2 Diabetes Mellitus Patients with High Risk for Cardiovascular Events - Leander, Derlin J.; Tahapary, Dicky L. (UI Scholars Hub, 2020)
Type 2 diabetes mellitus (DMT2) patients are associated with an increased risk of cardiovascular events. Prior to the era of cardio-vascular trial outcome (CVOT) evidence on the efficacy of old oral diabetes (OAD) drugs such as metformin, sulfonylurea, thiazolidindion, glinid, and alpha glucosidase inhibitors in reducing the risk of cardiovascular events was very limited. Since 2008, all OADs must have CVOT data. DPP-4 inhibitors are neutral against the risk of cardiovascular events while SGLT-2 inhibitors are reported to significantly reduce the risk of cardiovascular events. This finding even helped to change the DMT2 management guidelines issued by American Diabetes Association (ADA-EASD) in late 2018. However, SGLT-2 inhibitor applications in Indonesia are likely to be constrained in terms of costs. When compared with an intensive multifactorial approach that seeks to reduce blood glucose, lipids, blood pressure, weight, and aspirin; it turns out that this multifactorial approach is associated with a lower risk of higher cardiovascular events and lower costs. In the JKN era, where quality control and cost control are needed, it seems that the multifactorial approach will still be the main choice in reducing cardiovascular events in people with T2DM in Indonesia.